STUDI PERENCANAAN DRAINASE AIR HUJAN PADA RUMAH SAKIT X - Aditya, Muhammad Fathur (SINERGI : Jurnal Riset Ilmiah, 2025)
This study designs a rainwater drainage system for Hospital X to prevent water stagnation and maintain optimal sanitation conditions. Field surveys and hydrological data, including rainfall data from the Karangploso Rain Station, were analyzed to determine the peak runoff and the required drainage channel capacity. The hydrological analysis resulted in a 5-year return period design rainfall of 107.54 mm using the Log-Normal distribution. Hydraulic calculations indicate that surface concrete drainage channels are the most suitable option, given the soil conditions and flow requirements. The drainage channel design was calculated using the rational method to determine the channel dimensions, resulting in three standard channel types: S1 (height 0.4 m and width 0.3 m), S2 (height 0.7 m and width 0.5 m), and S3 (height 0.9 m and width 0.6 m). This system has sufficient capacity to convey peak runoff without causing flooding, thereby improving the safety and operational comfort of the hospital. Future research is recommended to integrate wastewater management into the drainage design, so that rainwater and hospital wastewater can be managed in an integrated manner, safeguarding environmental health and meeting sanitation standards.